2021
DOI: 10.1186/s12893-021-01283-3
|View full text |Cite
|
Sign up to set email alerts
|

Does concurrent adenoidectomy or tonsillectomy affect the graft success rate of cartilage myringoplasty in adults?

Abstract: Background The objective of this study was to evaluate the graft success and hearing outcomes of concurrent adenoidectomy or tonsillectomy and myringoplasty. Methods Medical case notes were reviewed for all adult patients with dry perforations who had undergone myringoplasty, with or without concurrent throat surgery, from December 2015 to February 2018. The study population was divided into concurrent myringoplasty and throat surgery (Group A) and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 17 publications
0
1
0
Order By: Relevance
“…Four studies included in their reported data the information about prior adenectomy or adenotonsillectomy [44,46,48,57]. The reason behind the comparison is that frequent inflammation around the Eustachian tube may affect the success of tympanoplasty, which was not proved by our results (Suppl.…”
Section: Prior Adenectomy or Adenotonsillectomymentioning
confidence: 71%
“…Four studies included in their reported data the information about prior adenectomy or adenotonsillectomy [44,46,48,57]. The reason behind the comparison is that frequent inflammation around the Eustachian tube may affect the success of tympanoplasty, which was not proved by our results (Suppl.…”
Section: Prior Adenectomy or Adenotonsillectomymentioning
confidence: 71%